The Integration of Knowledge (IoK) Methodological Approach to Reforming the Development of Islamic Economics, Banking, and Finance (IEBF) in Light of Maqasid (Objectives) and Sustainable Development Goals (SDGs) - Jasmin Omercic (Global Review of Islamic Economics and Business, 2021)
The contemporary world has reached a critical stage of development that imposes reforms at the highest and grassroots levels. Humanity realized that the current lifestyle increasingly threatens their welfare. Hence, we perceive that the Integration of Knowledge (IoK) methodological approach to reforming the development of Islamic economics, banking, and finance (IEBF) is central to transforming such a conventional approach to life. A reformed IEBF would focus on the maqasid (objectives) of shariah and the SDGs. The qualitative nature of this paper appraises the IoK methodological approach through a methodological pluralism recognizing rational and revelational sources of knowledge. This also involves methods of library research and critical content analysis. Firstly, an introduction reveals the distinctiveness of the IoK methodological approach as a shift from and based on the Islamization of Knowledge (IOK) movement. Its potential to reform IEBF becomes apparent because of common philosophical foundations like IOK’s. We highlight in brief the IEBF compatibility with and to reform via the IoK methodological approach and so attain targeted maqasid and SDGs. Secondly, a review of extant literature explains why the IOK and IE represent the solution to reform IEBF in contemporary times, to overcome mainstream economic, financial, and banking issues, and to fulfil maqasid and SDGs. Thirdly, findings show how the philosophical foundations of IOK represent the basis for future IEBF development via the IoK methodological approach. Moreover, we identify IoK methodological principles to appraise theories for IEBF development in light of the maqasid and SDGs agenda. Lastly, we conclude and provide actionable recommendations.